ドライバレー エンコ カラ ブンリ シタ ビセイブツ ト ソノ セイソク カンキョウ - 和栗, 修; ワグリ, オサム; WAGURI, Osamu (国立極地研究所, 1976)
P(論文) ドライバレー地域に存在する不凍塩湖の溶存ガス分析および微生物の検出を試みるために,1974-75年ドライバレー掘削計画の日本隊に参加した.ボニー,フリクセル,バンダ湖を中心にその他,マクマードサウンド内でも試料を採集した.溶在ガスは,ボニー東,西,フリクセル,バンダ湖でO_2,N_2,CO_2,Arが検出され,ボニー西,バンダ湖ではCH_4および未知ガス成分(m/e22)も検出された.真菌類はボニー東湖底層水でDiheterospora catenulataが分離された.フリクセル湖湖縁水でAureobasidium foliicolumと2種の酵母が分離され,その他地域で13種分離できた.これらの内14種は南極大陸で初めて検出されたものである.細菌はフリクセル湖でのみ2種以上検出された.1種はグラム陽性杆菌であり,もう1種はstalkをもったビブリオ状グラム陰性菌であり,このstalkをもった細菌はCaulobacterの1種と考えられるが,Caulobacterは南極大陸からは全く検出されておらず,分離された細菌は形態または生理的性状から新種であると思われる. Isolation of microorganisms and determination of gases dissolved in waters of unfrozen salt lakes in the Dry Valley of Antarctica were carried out, as part of the Dry Valley Drilling Project (DVDP) of the Mc-Murdo Sound region during the 1974-1975 summer season. Samples were collected in and around the Lakes Bonney, Fryxell and Vanda. Gas-chromatographic and GC-Mass spectrometric analysis of these liquid gaseous samples revealed oxygen, nitrogen and carbon dioxide from in waters of all lakes, and methane and unknown gas (m/e 22) were detected in waters of Lakes Bonney west lobe and Vanda. Eumycetes were isolated from the samples collected one species from the bottom water of Lake Bonney east lobe, three species from surface water of Lake Fryxell and thirteen species from other samples than from salt lakes. Fourteen species of these isolates have not been reported before from Antarctica. Two or more species of bacteria were isolated from the bottom water of Lake Fryxell. One species was gram-positive rods and the other was gram-negative vibrio type bacterium with stalk. The stalked bacterium seems to be an unknown species of Caulobacter. Reports of the isolation of bacteria of this type in Antarctic samples have not been published to date. departmental bulletin paper